2018
DOI: 10.1007/s12026-018-9010-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunological role of CD4+CD28null T lymphocytes, natural killer cells, and interferon-gamma in pediatric patients with sickle cell disease: relation to disease severity and response to therapy

Abstract: Sickle cell disease (SCD) is associated with alterations in immune phenotypes. CD4CD28 T lymphocytes have pro-inflammatory functions and are linked to vascular diseases. To assess the percentage of CD4CD28 T lymphocytes, natural killer cells (NK), and IFN-gamma levels, we compared 40 children and adolescents with SCD with 40 healthy controls and evaluated their relation to disease severity and response to therapy. Patients with SCD steady state were studied, focusing on history of frequent vaso-occlusive crisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Our results showed low frequencies of NK and NKT cells in SCA patients at steady state. In ElAlfy et al's [66] study, they showed that NK cell frequency was higher in all patients with SDC compared with controls, but the difference was not significant. Furthermore, they showed elevated counts of NK cells with higher levels of IFN-γ, so these cells were activated in SCA patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results showed low frequencies of NK and NKT cells in SCA patients at steady state. In ElAlfy et al's [66] study, they showed that NK cell frequency was higher in all patients with SDC compared with controls, but the difference was not significant. Furthermore, they showed elevated counts of NK cells with higher levels of IFN-γ, so these cells were activated in SCA patients.…”
Section: Discussionmentioning
confidence: 93%
“…Sickle cell disease (SCD) is associated with alterations in immune phenotypes [66], and we decided to evaluate NK and NKT frequencies on SCA patients at steady state. Recently, ischemia-reperfusion injury (IRI) with resultant white cell activation has been implicated as an additional contributor to the pathophysiology of SCD [67].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was relied upon 95% CI with 80% power, using unpaired t-test and assuming a (two-sided) α of 0.05. Based on previous study (El-Alfy et al, 2018) [11], Mean of CD4+ T lymphocytes (%) for SCD patients group was 34.41 while that of healthy control group was 30.0 and SD was 6.1 (of patients or control) with group size ratio of 1/1, the number of participants was 30 for each group.…”
Section: (C) Flow Cytometric Analysismentioning
confidence: 92%
“…Immune recovery post-HCT is crucial to avoid short and longterm infectious complications. Sickle cell disease patients have disease-specific infectious risk secondary to splenic dysfunction, although splenic phagocytic recovery has been reported in post-HCT period in some patients [94]. Infectious complications are increased following both TCD and TCR haplo-HCT secondary to intense immunoablation and subsequent delayed immune reconstitution [16][17][18].…”
Section: Immune Reconstitution Following Haplo-hct For Sickle Cell DImentioning
confidence: 99%
“…The use of cytokines to boost T-cell subsets is being pioneered in allogeneic transplant to address disease relapse and should be developed for non-malignant diseases to improve pathogen-specific immunity and engraftment. The role of natural killer cell killer immunoglobulin-like receptor ligand mismatching is also underexplored in sickle cell disease, though is important given the association between NK cells underlying sickle cell disease pathogenesis [94]. Multi-institution randomized trials comparing TCD and TCR approaches must be performed to truly know which platforms are preferred.…”
Section: Five-year Viewmentioning
confidence: 99%